2018
DOI: 10.5644/ama2006-124.196
|View full text |Cite
|
Sign up to set email alerts
|

Metformin use associated with protective effects for ocular complications in patients with type 2 diabetes – observational study

Abstract: <div class="WordSection1"><p><strong>Objective. </strong>The aim was to study the association of the use of an oral antihyperglycemic agent metformin with the presence of ocular complications in patients with type 2 diabetes (T2D). <strong>Methods. </strong>Medical records were reviewed for 234 patients with diagnosed T2D. 81.2% (n=190) patients were using metformin and 18.8% (n=44) using other oral antihyperglycemic agents. Plasma glucose concentration, glycated haemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 23 publications
3
26
1
Order By: Relevance
“…As age-related tissue effects changes significantly contribute to glaucoma development [4], the antiaging effect of metformin as a calorie restriction (CR) mimetic could delay the progression of disease [120]. Similar results were found in an observational study by Maleskic et al of 234 patients with T2DM, which showed that metformin was associated with decreased odds of POAG (OR = 0.33) compared to other anti-hyperglycaemic agents (p = 0.017) [15]. Interestingly a separate study, in which metformin use was significantly associated with elevated IOP in participants using a high dose (>2 g/day/year), systemic use of metformin was associated with a reduced risk of POAG, in a duration-dependent manner [121].…”
Section: Metforminsupporting
confidence: 59%
See 1 more Smart Citation
“…As age-related tissue effects changes significantly contribute to glaucoma development [4], the antiaging effect of metformin as a calorie restriction (CR) mimetic could delay the progression of disease [120]. Similar results were found in an observational study by Maleskic et al of 234 patients with T2DM, which showed that metformin was associated with decreased odds of POAG (OR = 0.33) compared to other anti-hyperglycaemic agents (p = 0.017) [15]. Interestingly a separate study, in which metformin use was significantly associated with elevated IOP in participants using a high dose (>2 g/day/year), systemic use of metformin was associated with a reduced risk of POAG, in a duration-dependent manner [121].…”
Section: Metforminsupporting
confidence: 59%
“…Metformin, a biguanide derivate commonly used in patients with type 2 diabetes, has come to be a front-runner recently in addressing this need, following a line of publications linking its use in a diabetic population with reduced incidence of POAG [14,15]. The cellular mechanism through which metformin is acting to combat glaucoma is not yet understood but likely involves effects on the pathogenesis of fibrosis and mitochondrial bioenergetic dysfunction in glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that the increased risk of glaucoma in patients with diabetes is due to increased corneal stiffness, corneal hysteresis, and enlargement of the optic cup. [ 9 ] In our study, IOP was found to be increased in diabetics than the nondiabetics whereas there was no difference in VCDR among diabetics and non-diabetics.…”
Section: Discussioncontrasting
confidence: 44%
“…[ 3 4 5 ] AMPK upregulation alters the tone of cells in the trabecular meshwork, thus lowering the IOP and preventing the progression of glaucoma. [ 6 7 ] Preliminary results from animal studies have also shown that metformin exerts neuroprotective effect by upregulation of AMPK. Metformin regulates the methylation at cellular levels and promotes ganglion cell survival.…”
mentioning
confidence: 99%
“…Maleškić et al . [ 6 ] postulated that the gero-protective effect of metformin could delay tissue damage, which can be a major factor in delaying the progression of glaucoma. Lin et al .…”
mentioning
confidence: 99%